The Role of Organizational Learning Culture and Workplace Empowerment in Improving Workplace Spirituality through Knowledge Sharing Behavior as a Mediation Variable - Nurcahyo, Satria Avianda; Rachmawati, Meida (UNISSULA, 2024)
This research aims to find the role of Organizational Learning Culture and Workplace Empowerment on Workplace Spirituality through Knowledge Sharing Behavior as a mediating variable in PT. Sidomuncul herbal medicine industry, Semarang Regency. This research is quantitative research using the Partial Least Square SEM PLS application tool, carried out to test hypotheses with the aim of strengthening the hypothesis or rejecting theories or hypotheses from existing research results. the population was permanent employees at PT. Sidomuncul herbal medicine industry, Semarang Regency. The Human Capital Technology Division and Market Capability Division were deemed suitable for the Knowledge Sharing Behavior variable, totaling 255 people consisting of 200 male employees and 55 female employees. The sampling technique used in this research is census with the aim of the total population being used to determine the sample size, the research used a census technique of 255 respondents. The results of this research prove that Knowledge Sharing Behavior has a positive and significant effect on Workplace Empowerment, Knowledge Sharing Behavior has a positive and significant effect on Workplace Spirituality, that Organizational Learning Culture has a positive and significant effect on Knowledge Sharing Behavior, that Organizational Learning Culture has a positive and significant effect on Workplace Spirituality, Knowledge Sharing Behavior can greatly mediate the influence of Organizational Learning Culture on Workplace Empowerment.